Biphenyl liquid crystal epoxy containing flexible chain: Synthesis and thermal properties. Issue 38 (28th February 2020) - Zhang, Qian; Chen, Guokang; Wu, Kun; Shi, Jun; Liang, Liyan; Lu, Mangeng
Abstract: A biphenyl type liquid crystal epoxy (LCE) monomer 4, 4′‐di(2, 3‐epoxyhexyloxy)biphenyl (LCBP4) containing flexible chain was synthesized and the curing behavior was investigated using 4, 4′‐diaminodiphenylmethane (DDM) as the curing agent. The effect of curing condition on the formation of the liquid crystalline phase was examined. The cured samples show good mechanical properties and thermal stabilities. Moreover, the relationship between thermal conductivity and structure of liquid crystalline domain was also discussed. The samples show high thermal conductivity up to 0.28–0.31 W/(m*K), which is 1.5 times as high as that of conventional epoxy systems. In addition, thermal conductive filler, Al2 O3, was introduced into LCBP4/DDM to obtain higher thermal conductive composites. When the content of Al2 O3 was 80 wt%, the thermal conductivity of the composite reached to 1.86 W/(m*K), while that of diglycidyl ether of bisphenol A (Bis‐A) epoxy resin/DDM/Al2 O3 was 1.15 W/(m*K). Compared with Bis‐A epoxy resin, the formation of liquid crystal domains in the cured LCE resin enhanced the thermal conductivity synergistically with the presence of Al2 O3 . Furthermore, the introduction of Al2 O3 also slightly increased the thermal stabilities of the cured LCE. Abstract :